Drawn to nature Gilbert White and the artists - Martin, Simon 1979- (Pallant House Gallery, 2021)
Since its publication in 1789, Gilbert White's Natural History and Antiquities of Selborne has inspired generations of artists, writers and naturalists. From Thomas Bewick to Eric Ravilious and Clare Leighton, many artists' depictions of animals, birds and wildlife have illustrated White's celebrated book, together providing a microcosm of natural history illustration from the eighteenth century until today. In Drawn to Nature, Simon Martin has gathered joyful and beautiful images of the extraordinary array of wildlife described by White, providing an insight into the continuing appeal and relevance of the Natural History. This fascinating account takes us from some of the earliest published depictions of birds and animals, to pioneering nature photography, the revival of wood-engraving in the 1920s and 30s, and responses to White's message about the natural world by contemporary illustrators such as Angie Lewin and Emily Sutton. The book also includes an introduction to the life of Gilbert White by Sir David Attenborough, an essay by Virginia Woolf, poems by modern and contemporary poets, and a jacket design by Mark Hearld. Exhibition: Pallant House Gallery, Chichester, UK (05.08. - 14.11.2020)
Keywords: White, Gilbert -- 1720-1793 -- Natural history and antiquities of Selborne, in the county of Southampton; Geschichte 1790-2020; Tierdarstellung; Kunst; Rezeption; Illustration; Großbritannien; White, Gilbert / 1720-1793 / Natural history and antiquities of Selborne, in the county of Southampton; Natural history and antiquities of Selborne, in the county of Southampton (White, Gilbert); Natural history / Pictorial works; Animals / Pictorial works; Illustration of books / Great Britain; Animals; Illustration of books; Natural history; Pictorial works; Great Britain